2017
DOI: 10.1097/gox.0000000000001318
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Surgical Autonomy in a Plastic Surgery Resident Clinic

Abstract: Background:Resident clinics are thought to catalyze educational milestone achievement through opportunities for progressively autonomous surgical care, but studies are lacking for general plastic surgery resident clinics (PSRCs). We demonstrate the achievement of increased surgical autonomy and continuity of care in a PSRC.Methods:A retrospective review of all patients seen in a PSRC from October 1, 2010, to October 1, 2015, was conducted. Our PSRC is supervised by faculty plastic surgery attendings, though pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…As this is a prominent model referred to in the surgical education literature, 3,4 it is noteworthy exploring it in greater depth, particularly as it has been tabulated into stages/levels that trainees can resonate with in plastic surgery. 3234 In fact, the PSMP levels/milestones were guided by the Dreyfus Model. 33,35…”
Section: Defining the Dreyfus Model In Plastic Surgery Practicementioning
confidence: 99%
“…As this is a prominent model referred to in the surgical education literature, 3,4 it is noteworthy exploring it in greater depth, particularly as it has been tabulated into stages/levels that trainees can resonate with in plastic surgery. 3234 In fact, the PSMP levels/milestones were guided by the Dreyfus Model. 33,35…”
Section: Defining the Dreyfus Model In Plastic Surgery Practicementioning
confidence: 99%
“…Furthermore, graduated chief residents were surveyed and reported significant value in the surgical experience, operative autonomy, medical knowledge and ACGME core competencies afforded by supporting a resident run clinic. These findings have been echoed in other studies as well in the settings of a resident-run aesthetic clinic [80] which demonstrated a structured, autonomous experience in rhinoplasty with acceptable complication rates as well as good satisfaction as rated by both patients and residents [81].…”
Section: Outcomes Associated With Autonomymentioning
confidence: 59%
“…In regard to plastic surgery resident clinics, they continue to be an arena for the development of senior resident autonomy, decision-making, and maturation. 23 Increased case volume and autonomy have been shown to increase resident confidence and competence, 24 and resident clinics provide an ideal avenue for this. Various resident clinic models have been proposed, 23 , 25 28 with residents consistently supporting the importance of their role in training.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Increased case volume and autonomy have been shown to increase resident confidence and competence, 24 and resident clinics provide an ideal avenue for this. Various resident clinic models have been proposed, 23 , 25 28 with residents consistently supporting the importance of their role in training. Despite concerns with patient safety in resident clinics, multiple studies have validated the safety and complication profiles in this setting.…”
Section: Discussionmentioning
confidence: 99%